Whip it into shape: Revision of the Demansia psammophis (Schlegel, 1837) complex (Squamata: Elapidae), with a description of a new species from central Australia - Nankivell, James H.; Maryan, Brad; Bush, Brian G.; Hutchinson, Mark N. (Zootaxa, 2023)
The genus Demansia Günther is the most diverse genus of Australian terrestrial elapids. A phylogenetic framework for the familiar but problematic taxa D. psammophis and D. reticulata (Gray) has been long overdue to ascertain interspecific relationships and resolve unclear taxonomic issues. Here we present an integrated molecular phylogenetic and morphological analyses to review species delineation, resulting in confirmation that both D. psammophis and D. reticulata are full species and that some populations referred to D. r. cupreiceps Storr are not distinguishable from more typical D. reticulata. We also find the widespread central Australian population (treated by most authors as part of cupreiceps) to be specifically distinct. We redescribe D. psammophis and D. reticulata to clarify morphological and geographical boundaries and describe D. cyanochasma sp. nov. based on a combination of molecular genetic markers, details of colour and pattern, adult total length and a few morphometric attributes. We also designate a lectotype for D. psammophis from the original syntype series and comment on the necessity for further taxonomic refinement of this distinctive group.